The impact of nurse-led annual telephone follow-up of patients with inflammatory bowel disease - Bager, Palle (BMJ Qual Improv Rep, 2014)
Inflammatory bowel diseases (IBD) are characterised by periods of disease activity and period with disease in remission. In Denmark all patients are seen in hospital settings. The aim of this study was to introduce a nurse-led phone service for stable patients replacing annual visits. The study originated from an outpatient cohort of 1,600 patients with IBD. A research protocol was determined before the intervention was launched, which included surveys among the patients before the intervention, after the intervention, collection of longitudinal data in a three year period, and a clinical audit. Budget impact analysis (BIA) and cost-effectiveness analysis (CEA) were done. Furthermore, the staff evaluated the process. Almost 30% (n = 474) of the total cohort was enrolled in the service. Eighty-seven per cent of the patients welcomed the phone service beforehand. After implementation, 94% of the patients included were pleased with the service. The programme has shortened the waiting time for most other services, but no improvement in the workload was observed. The BIA showed limited savings. The CEA showed an annual saving of 100€ per patient when using the annual phone service over routine visits. In conclusion, changing the method of contact from routine annual visits to annual phone calls from a nurse was feasible and well accepted for stable patients with IBD. The benefits of the service were most marked for the patients.